Oxymorphone extended release does not affect CYP2C9 or CYP3A4 metabolic pathways - Adams, Michael; Pieniaszek, Jr, Henry J; Gammaitoni, Arnold R; Ahdieh, Harry (Journal of clinical pharmacology, 2005)
Two 14-day, randomized, open-label, parallel-group studies examined the effects of extended-release (ER) oxymorphone on CYP2C9 or CYP3A4 metabolic activities in healthy subjects. On days -1, 7, and 14, subjects received either a CYP2C9 probe (tolbutamide 500 mg) or CYP3A4 probes (midazolam and [14C N-methyl]-erythromycin for the erythromycin breath test). Subjects were randomized to 5 groups: high-dose oxymorphone ER (3 x 20 mg q12h) + naltrexone (50 mg q24h); low-dose oxymorphone ER (10-20 mg q12h); rifampin (2 x 300 mg q24h), an inducer of CYP2C9 and CYP3A4 activities; naltrexone (50 mg q24h); or CYP probes alone (controls). Probe metabolism was significantly altered by rifampin on days 7 and 14 (P < .05), whereas probe metabolism was not significantly affected by low-dose oxymorphone ER or by high-dose oxymorphone ER plus naltrexone. Oxymorphone ER exhibits a minimal potential for causing metabolic drug-drug interactions mediated by CYP2C9 or CYP3A4.